Synthesis Protocols of the Most Common Layered Carbide and Nitride MAX Phases. Issue 3 (5th February 2020) - Haemers, Joachim; Gusmão, Rui; Sofer, Zdeněk
Abstract: MAX phases represent a large group of carbide‐ and nitride‐layered ternary compounds. Their general formula is M n +1 AX n, where n = 1–3, M is an early transition metal, A is an A‐group element, and X is either carbon or nitrogen. The MAX phases combine properties of metals (good electrical and thermal conductivity, machinability, low hardness, thermal shock resistance, and damage tolerance) with those of ceramics (high elastic moduli, temperature strength, and oxidation and corrosion resistance). Publications on MAX phases have increased considerably in recent years. A late development causing heightened interest in MAX phases is the possibility by which these can be selectively etched to MXenes by removal of the A‐group element. In view of optimizing properties for prospective applications, the synthesis protocols of some of the most common carbide and nitride MAX phases are reviewed. Characterization of their physical, mechanical, and corrosion/oxidation properties is also discussed. Recent developments have revealed the potential for further practical application and have led to accessible strategies to synthesize new MAX phases using the pressure‐less sintering, spark plasma sintering, or molten salt routes. Abstract : Different approaches and practices used to synthesize and characterize ternary M n +1 AX n, with 1<n<3, in which M is an early transition metal, A is an A‐group element, and X is C or N. The provided overview can be of great use for broader access to synthesis methods and the developments in the applications of MAX phases.